CONCOMITANT SEXUALLY TRANSMITTED DISEASES IN PATIENTS WITH DIAGNOSED HIV/AIDS: A RETROSPECTIVE STUDY - Harnanti, Densy Violina; Hidayati, Afif Nurul; Miftahussurur, Muhammad (African Journal of Infectious Diseases (AJID), 2018)
Background: Human immunodeficiency virus (HIV) is a virus that causes Acquired Immunodeficiency Syndrome (AIDS) which weaken the human immune system and thus increasing the incidence of sexually transmitted infections (STIs) and vice versa.Materials and Methods: A retrospective study of STIs in HIV/AIDS patients in Unit Perawatan Intermediate Penyakit Infeksi (UPIPI) Dr. Soetomo General Hospital Surabaya was conducted from January 1st, 2013 to December 31st, 2014. We examined the number and type of STIs, age distribution, gender, occupation, number of CD4+, and antiretroviral treatment of patients with HIV/AIDS. The data were presented in a descriptive analysis.Results: The percentage of STIs patients was 4.2% (148 of 3.350) of all patients with HIV/AIDS in the UPIPI Outpatient Clinic of Dr. Soetomo General Hospital. Most patients were 25-44 years old (70.9%) including 54.7% were males, 8.0% were housewives, and 1.4% were students. The five highest prevalence of STIs were condylomata acuminate (43.9%), non-specific genital ulcers (11.5%), syphilis (10.7%), genital herpes (10.1%), and scabies (8.1%). The sexual predilections consisted of heterosexual (70.9%), homosexual (12.2%), bisexual (2.0%), and no data (14.9%). Patients with the number of CD4+ <200 mm3 was 52.0% and 79.1% of the patients received ARV therapy.Conclusion: STIs and HIV/AIDS were closely related. HIV/AIDS could increase the incidence of STIs and STIs could elevate HIV/AIDS.